Angola : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in Angola during the 1990s. A major decline in economic conditions occurred in 1993, in the wake of the resumption of the civil war. In 1993, inflation reached unprecedented levels, overall GDP declined by an estimated 24 percent in real terms, and oil production experienced a downturn for the first time, in part as a result of the destruction of a major onshore oil facility. Export earnings from crude oil were also hit by the decline in world oil prices. Nevertheless, the economy became increasingly dependent on oil.